Program for Simulation and Testing of Apply Cryptography of Advance Encryption Standard (AES) Algorithm with Rivest-Shamir-Adleman (RSA) Algorithm for Good Performance - Pattanavichai, Santi (International Journal of Electronics and Telecommunications, 2022)
Nowadays, information security management systems are important parts of managing a system for better handling of the information security. In scenarios and situations where safety management is done by managing protection of malwares, it is important to manage security issues properly. Cryptography is an approach which makes possible for a recipient to encrypt and decrypt the information. A combination of two different strategies for encryption and decryption in the text encoding will be transformed into the used all content. The encryption and decryption key of the content decryption key is used. There are different types of information. A number, such as finding two large prime numbers with that product. The number, the size of the RSA key is large enough to make, it's hard to pinpoint these numbers. The key, known as the RSA public key, is the most prominent open encryption. Calculations were used for information exchange. In this paper, we created a program for simulation and testing of apply cryptography of Advance Encryption Standard (AES) algorithm with Rivest-Shamir-Adleman (RSA) algorithm for better performance. In this study, this program is an application of a new algorithm to be the AES&RSA principle of using a public key instead of a private key for cryptography, and the testing of encryption and decryption for the AES&RSA algorithm resulted in time is no different on the AES algorithm and more secure encryption and decryption. The results indicated that the time needed for encoding and decoding of AES&RSA algorithm has been reduced (i.e., efficiency has been improved).